IMPLEMENTASI PROGRAM DESA MAJU INHIL JAYA (DMIJ) DI KABUPATEN INDRAGIRI HILIR - Agustiningrum, Gita; As’ari, Hasim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The program of Desa Maju Inhil Jaya (DMIJ) is a district government program that has the aim of providing legal guarantees and certainty to the right and obligations of everyone to be involved and involve themselves in the process of managing development in the village. This study aims to find how the implementation of Desa Maju Inhil Jaya (DMIJ) Program in Indragiri Hilir District and the factors that inhibited it. The theory used is theory of implementation program by Charles O. Jones, there are three indicators that affect implementation: organization, interpretation, and application (expectation). This study uses a type of qualitative research with a phenomenological approach and the data needed both primary and secondary were obtained through interviewing, observation and documentation techniques for further analysis of data using descriptive data analysis techniques. The results of this study indicate that, first implementation of Desa Maju Inhl Jaya (DMIJ) Program in Indragiri Hilir district has not been optimal from organizational structure, program implementers, coordination schedule of activities and performance. Second, the factors that hinder the implementation of Desa Maju Inhil Jaya (DMIJ) Program in Indragiri Hilir district are human resource, coordination, communication, and control ranges.Keywords: Desa Maju Inhil Jaya, Public Policy, Implementation, Program